Characterization of the attention to the Occupational Health in the Policlínico Juan José Apolinaire Pennini. Cienfuegos 2018. - Yoleysi Arteaga Cuéllar; Pedro Luis Veliz Martínez; Sarah Hernánez Malpica; Noelia Castro Ladrón de Guevara; Leticia Castro Morejón; Pedro Ricardo Borges Cabrera (Medisur)
Background: considering that work accidents constitute a large source of cost generation and that in Cuba there is an aging age distribution, health care for workers is a fundamental process in primary health care. Objective: to characterize occupational health care at the Juan José Apolinaire Pennine Polyclinic in Cienfuegos. Methods: descriptive, cross-sectional study carried out in 2018. The sample made up of workers from the Carlos Manuel de Céspedes Thermoelectric Plant, chosen by simple random sampling, and doctors and nurses from the polyclinic family, intentionally selected. To obtain the information, two instruments were used, one applied to health personnel, to identify knowledge about occupational health and the other to the workers of the selected company to determine perceived satisfaction with the care received. Results: in the professionals of the Juan José Apolinaire Pennini polyclinic in Cienfuegos, there is evidence of a lack of knowledge about occupational health, by not showing clarity about occupational risks, causes of work accidents, examinations to be carried out in the working population and criteria for declaring an occupational disease . In addition, the surveyed patients are moderately satisfied with the care received, mainly due to deficiencies in stability, need and comprehensiveness of care. Conclusions: the research results suggest that there is a relationship between the lack of knowledge about occupational health in polyclinic workers and the insufficient attention perceived by the surveyed patients.